Penerapan Pidana Tambahan Dalam Kuhp Baru: Kebiri Kimia Dan Publikasi Identitas Pelaku Percabulan Anak - Suciara, Angelica; Idias, Bryan; Siregar, Nathasya Jhonray; Siregar, Tasya Amira Frananda; Prabowo, Tri Widyasto (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Several countries have implemented policies of chemical castration and the publication of the identities of child sex offenders as preventive measures and to protect the public. Chemical castration is applied in countries such as the United States, although its implementation varies depending on the laws of each individual state. In Poland, chemical castration is mandatory for offenders who have committed sexual crimes against children under the age of 15. South Korea also enforces a similar policy for offenders targeting children under the age of 16. Meanwhile, in Russia, chemical castration is carried out on a voluntary basis. On the other hand, the publication of offenders’ identities is also a form of additional punishment adopted in several countries. The United States has a Sex Offender Registry system that allows the public to access information about individuals convicted of sexual offenses. The United Kingdom applies the Child Sex Offender Disclosure Scheme, which permits authorities to disclose the identity of offenders to parents or concerned parties. Canada also allows the publication of offender identities for those considered high-risk, aiming to increase public awareness and vigilance.